ТИПОЛОГІЧНИЙ АНАЛІЗ ЗАКАЗНИКІВ БУКОВИНИ - Решетюк, О.В. (Київський національний університет імені Тараса Шевченка, ВПЦ "Київський університет", 2016)
There has been executed valuing of wildlife preserves representation in Chernowitsky-region's net with the safe objects. The typological analysis of existing Bukovina's wildlife preserves system has been done. The wildlife preserves even assignment at administrate and physic-geographic districts of region has been analyzed. Coefficients of separate districts' insularities have been determined for region ecological stability ascertain. Rather low nature-safe index of wildlife preserve's category at region has been fixed (0.01–0.26). The author offers increase wildlife preserves' net with valuable rare landscapes. These would give resources for Bukovina's nature-save net to widen as much as 171.8 th.ha (21.2% of region's territory).
Keywords: reserve, representativeness, insularities, environmental index, biodiversity